Applicability and limitations of potassium-related classical geothermometers for crystalline basement reservoirs. (March 2020) - Li, Jiexiang; Sagoe, Gideon; Li, Yilian
Highlights: The imbalance of the Na-K ion-exchange and mixing may influence its accuracy of the Na-K geothermometer. The K-Mg geothermometer is not suitable for obtaining temperatures in high temperature reservoirs (> about 150 °C). The Na-K-Ca geothermometer may play a complementary role for evaluating reservoir temperatures above 200 °C. An improved Na-K-Mg triangular diagram modified from Giggenbach (1988) was presented to choose the most suitable geothermometers. Abstract: Although potassium-related classical geothermometers have been widely used over the years to estimate the temperature of geothermal reservoirs, there are limitations regarding their practical applications. In order to obtain more reliable reservoir temperature estimates, the limitations and the advantages of classical geothermometers must be realized and understood prior to their selection and application. In this study, the hydrogeochemical data for 239 water samples from geothermal wells drilled into crystalline basement reservoirs across the world were collated and analyzed to obtain the applicability conditions of K-related classical geothermometers from the scientific literature. Of these samples, 44 are of special interest being unaffected by mixing and because their reservoir temperature is known. The study shows that generally, the Na-K geothermometer gives valid estimates of reservoir temperatures above 200 °C. However, that is not the case in lower-temperature reservoirs since the equilibrium between albite, K-feldspar, and the aqueous solution is not always achieved, and the Na-K ratio of the primary fluids in the host reservoirs may change due to mixing taking place during the ascent of these thermal waters which have relatively low Na and K concentrations. At high temperatures, especially above 250 °C, reservoir temperature calculations for the use of the K-Mg geothermometer showed relatively large deviations from the measured temperatures. The K-Mg geothermometer seems to work well for mid-low temperature reservoirs (below around 150 °C), and the deviations from the reservoir temperatures probably result from the low activities of clinochlore in chlorites. Moreover, the performance of the K-Mg geothermometer is negatively affected by mixing of the thermal waters with other kinds of groundwater. The Na-K-Ca geothermometer may play a complementary role for evaluating reservoir temperatures above 200 °C but should be applied with caution when calcite precipitation triggered by degassing of the thermal waters takes place.